2014
DOI: 10.1161/strokeaha.114.006575
|View full text |Cite
|
Sign up to set email alerts
|

Trends Over Time in the Risk of Stroke After an Incident Transient Ischemic Attack

Abstract: Background and Purpose-Long-term population trends in the early risk of stroke after transient ischemic attack (TIA) are unknown. We hypothesized that there has been an appreciable decline in the risk of stroke after TIA for the last decade. Methods-Population-level cohort study from Victoria, Australia (population 5.6 million), using linked data from hospitals, emergency departments, and death records (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011), with a 2-year clearance period to define … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 18 publications
3
48
2
Order By: Relevance
“…Stroke and transient ischemic attack hospitalization rates using discharge abstract database have been shown to be decreasing. [17][18][19] Although this finding is consistent with the advances in stroke knowledge and care, it is important to recognize that the decreased admissions for transient ischemic attacks may be largely explained by practice variations: more patients with mild or transient symptoms are being evaluated and discharged from the emergency departments without admission. Physicians must recognize that they are active participants in administrative health data generation, and coding is limited by documentation quality.…”
Section: July 2016mentioning
confidence: 54%
“…Stroke and transient ischemic attack hospitalization rates using discharge abstract database have been shown to be decreasing. [17][18][19] Although this finding is consistent with the advances in stroke knowledge and care, it is important to recognize that the decreased admissions for transient ischemic attacks may be largely explained by practice variations: more patients with mild or transient symptoms are being evaluated and discharged from the emergency departments without admission. Physicians must recognize that they are active participants in administrative health data generation, and coding is limited by documentation quality.…”
Section: July 2016mentioning
confidence: 54%
“…Hospital data linkage to other governmental database (non-hospital) such as Police Road Traffic Accident reports, PBS, MBS, ABS, Child Protection Service records make up 8% of reported data linkage while the remaining 36.2% were from non-specified birth or death records, registries, existing studies or survey populations. Most publications (73%) were descriptive and analytical epidemiological studies, such as those that assessed mortality from rheumatic heart disease on the Aboriginal Australian population, 29 time trends in risk of stroke among elderly Victorians 30 and studies exploring respiratory infection hospitalisations for children. 31 The smallest contributions came from costing studies, economic evaluations, healthcare evaluations and those informing health services planning (12.9%); the rest were validation studies (13.7%).…”
Section: Resultsmentioning
confidence: 99%
“…10 Several studies have described the prognosis of TIAs and minor strokes. Some are population based, [11][12][13][14] whereas others have reported on patients presenting to hospitals and emergency departments. [15][16][17][18][19] Most outpatient studies were conducted before the establishment of daily rapid access TIA clinics based on the EXPRESS study 6 model.…”
mentioning
confidence: 99%
“…Many recent TIA studies have reported 90-day outcomes. 11,20,21 Ten-year results of the OXVASC Study are also available. 22 Up to 60% of patients referred to TIA clinics by nonspecialists turn out to be TIA mimics.…”
mentioning
confidence: 99%